2015
DOI: 10.1089/chi.2014.0132
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Primary Care Intervention on Body Mass Index: The Maine Youth Overweight Collaborative

Abstract: Background: We evaluated the impact of a brief primary-care-based intervention, The Maine Youth Overweight Collaborative (MYOC), on BMI (kg/m 2 ) z-score change among participants with obesity (BMI ‡ 95th percentile for age and sex), overweight (BMI ‡ 85th and < 95th percentile), and healthy weight ( ‡ 50th and < 85th percentile).Methods: A quasi-experimental field trial with nine intervention and nine control sites in urban and rural areas of Maine, MYOC focused on improvements in clinical decision support, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…However, no between-group differences were seen in BMI [38], which is consistent with findings from other family-based interventions [22,25]. The Maine Youth Overweight Collaborative (MYOC) programme study's primary aim was to evaluate the impact of a brief primary-carebased intervention on BMI-z score for healthy, overweight and obese children [39]. The healthcare provider delivered the '5,2,1,0' healthy habits message (five servings or more of fruit and vegetables; 2 hours or less of screen time; 1 hour or more of PA; and zero sugar-sweetened beverages [SSBs] daily) during one well-child visit.…”
Section: Primary Care Based Settingsupporting
confidence: 65%
See 1 more Smart Citation
“…However, no between-group differences were seen in BMI [38], which is consistent with findings from other family-based interventions [22,25]. The Maine Youth Overweight Collaborative (MYOC) programme study's primary aim was to evaluate the impact of a brief primary-carebased intervention on BMI-z score for healthy, overweight and obese children [39]. The healthcare provider delivered the '5,2,1,0' healthy habits message (five servings or more of fruit and vegetables; 2 hours or less of screen time; 1 hour or more of PA; and zero sugar-sweetened beverages [SSBs] daily) during one well-child visit.…”
Section: Primary Care Based Settingsupporting
confidence: 65%
“…Results showed no impact of the intervention on BMI z-score for participants aged 5-18 years, in the healthy weight (50 th -85 th percentile, n = 506) or overweight (85 th -95 th percentile, n = 216) categories. A shortcoming of this intervention, was its duration; one, 4-6 minute visit is unlikely, on its own, to improve BMI [39].…”
Section: Primary Care Based Settingmentioning
confidence: 99%
“…This is supported by the literature which has shown that increases in screen time are associated with increased odds of overweight/obesity ( Dennison et al, 2002 ), including longitudinally ( Hesketh et al, 2007 ). Previous studies have similarly shown no associations between the collective attainment of the ‘5-2-1-0’ recommendations and BMI both in cross-section ( Schrempft et al, 2015 ) and longitudinally ( Gortmaker et al, 2015 ).…”
Section: Discussionmentioning
confidence: 76%
“…Few studies have examined adherence to the ‘5-2-1-0’ recommendations collectively and assessed predictors of attainment ( Foltz et al, 2011 , Kunin-Batson et al, 2015 , Rogers et al, 2013 , Haughton et al, 2016 , Gonzalez et al, 2015 , Iannotti and Wang, 2013 , Briefel et al, 2015 , Turer et al, 2013 ). Furthermore, there is a paucity of studies that have assessed the association of ‘5-2-1-0’ recommendations with BMI z-score or weight status in preschool-aged children ( Schrempft et al, 2015 , Gortmaker et al, 2015 ), which is important to consider given that 80% of children in this age group use screens daily ( Rideout et al, 2003 ). Of the studies examining adherence to the ‘5-2-1-0’ recommendations, most have relied on self-reported data ( Rogers et al, 2013 , Haughton et al, 2016 , Gonzalez et al, 2015 , Iannotti and Wang, 2013 , Briefel et al, 2015 ) and have focused on school aged children ( Kunin-Batson et al, 2015 , Rogers et al, 2013 , Haughton et al, 2016 , Gonzalez et al, 2015 ) or adolescents ( Foltz et al, 2011 , Haughton et al, 2016 , Iannotti and Wang, 2013 ) instead of preschoolers ( Briefel et al, 2015 , Turer et al, 2013 , Schrempft et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…29 -32 Three studies were excluded because of missing outcome data that the authors were unable to provide. [31][32][33] The final analysis included 13 articles reporting on 10 RCTs 12, 20 -28, 34 and 2 quasi-experimental studies. 29,30 All of the RCTs had missing methodological quality indicators.…”
Section: Search Resultsmentioning
confidence: 99%